2017
DOI: 10.5334/gjgl.56
|View full text |Cite
|
Sign up to set email alerts
|

Against information structure heads: A relational analysis of German scrambling

Abstract: This article argues against cascades of information-structural functional heads in the German middle field as an explanation for scrambling movements. Instead, we argue, some instances of scrambling correlate with sentence-level semantic effects, whereas other word order changes are affected by prosody and do not have any interpretative effects. An alternative architecture for scrambling is developed, which takes into account the clear empirical differences between these different subtypes of what is summarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…For proposals along these lines and relevant evidence, see e.g. Fox (2000), Chomsky (2001Chomsky ( , 2008a, Reinhart (2006), Struckmeier 2016 Note that unlike classical X-bar Theory, a LABEL-based system allows for the possibility that a constructed object K remains unlabeled (exocentric), e.g. when K is a root clause or created by operations that are not head-oriented in any plausible sense, such as syntactic scrambling.…”
mentioning
confidence: 99%
“…For proposals along these lines and relevant evidence, see e.g. Fox (2000), Chomsky (2001Chomsky ( , 2008a, Reinhart (2006), Struckmeier 2016 Note that unlike classical X-bar Theory, a LABEL-based system allows for the possibility that a constructed object K remains unlabeled (exocentric), e.g. when K is a root clause or created by operations that are not head-oriented in any plausible sense, such as syntactic scrambling.…”
mentioning
confidence: 99%
“…Witness also that Müller (2010) has shown that was - für splits out of external subjects improve when the object scrambles across the subject (10b). In this example, scrambling the object ( den Fritz ) results in a syntactic configuration that is preferred in cases where the subject ( was für Bücher ) is interpreted as focal; this is due to a complex interplay between syntax, prosody, and pragmatic interpretation (see Struckmeier, 2017 on this point):…”
Section: Constructions In Minimalism and Their Functional Motivationmentioning
confidence: 99%
“…Some linguists tend to argue that there simply must be differences in meaning associated with the different structures [and such linguists are found in both the functionally minded as well as the formal camp, e. g. in syntactic cartography; for some criticisms, cf. Struckmeier 2014Struckmeier , 2017Struckmeier , 2020]. While we do not want to pre-judge whether different meanings of distinguishable forms will be observed at some point in the future, we must not fail to point out that such meaning distinctions are clearly not readily perceivable (at least for the time being).…”
Section: Previous Work On Similar Questionsmentioning
confidence: 99%
“…The different word orders available in the German middle field thus do not strictly express information structural distinctions (like case markings helps express argument status). Rather, some authors assume (Bayer and Kornfilt 1994;Haider this volume;Fanselow 2001Fanselow , 2003Struckmeier 2014Struckmeier , 2017 that the grammar treats the word order as truly optional choices. But the use of these optionally available structures can still reflect discourse distinctions, maybe also in connection with the prosodic markings that also go into the computation of such discourse-related requirements.…”
Section: Previous Work On Similar Questionsmentioning
confidence: 99%